1992
DOI: 10.1088/0268-1242/7/4/012
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron resonance of the quasi-two-dimensional electron gas at Hg1-xCdxTe grain boundaries

Abstract: The magnetotransmission of a p-type Hg,,,,Cd,.,,,Te bicrystal containing a single grain boundary with an inversion layer has been investigated in the submillimetre wavelength range. For the first time t h e cyclotron resonance lines belonging to the various electric subbands of a quasi-two-dimensional carrier system at a grain boundary could be detected. The measured cyclotron masses and the subband densities determined from Shubnikov-de Haas experiments are compared with theoretical predictions and it is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Of importance for understanding the measured behavior of the resistance of graphite samples is the existence of well-defined interfaces between the single-crystalline regions. As we mentioned in the introduction, interfaces between crystalline regions in semiconductors with different orientations, for example [20][21][22][23], lead to confined quasi-2D carrier systems with a much larger carrier density than the bulk matrix. We assume therefore that these interfaces running parallel to the graphene layers of the graphite structure are the origin of metalliclike resistivity as well as of the apparent large carrier density measured in bulk samples, i.e.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of importance for understanding the measured behavior of the resistance of graphite samples is the existence of well-defined interfaces between the single-crystalline regions. As we mentioned in the introduction, interfaces between crystalline regions in semiconductors with different orientations, for example [20][21][22][23], lead to confined quasi-2D carrier systems with a much larger carrier density than the bulk matrix. We assume therefore that these interfaces running parallel to the graphene layers of the graphite structure are the origin of metalliclike resistivity as well as of the apparent large carrier density measured in bulk samples, i.e.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…As the results from various semiconductors show (e.g. n-Ge bicrystals [20,21], p-InSb [22] as well as in Hg 1−x Cd x Te grain boundaries [23]), internal interfaces lead to the formation of confined quasi-2D carrier systems with n 0 ∼ 10 12 -10 13 cm −2 and clear signs of the quantum Hall effect [21]. Recent studies have demonstrated the large sensitivity of the resistivity of graphite samples to the internal interfaces that exist between crystalline regions of ∼30-100 nm thickness, a few microns long and running mostly parallel to the graphene planes [19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand it is well known that grain boundaries in various semiconductors can lead to the formation of quasi-two dimensional carrier systems confined in the boundaries. As early examples in literature we refer to the quasi-two dimensional electron gas system that was found at the inversion layers of n-Ge bicrystals (Uchida et al, 1983;Vul & Zavaritzkaya, 1979) or in p-InSb (Herrmann et al, 1984) as well as in Hg 1−x Cd x Te grain boundaries (Ludwig et al, 1992). It is important to note that in Ge-bicrystals Uchida et al (1983) found actually the quantum Hall effect (QHE) at T 4.2 K and at magnetic fields above 6 T. The density of carriers at the interface was estimated to be ∼ 5 × 10 12 cm −2 .…”
Section: Influence Of the Internal Microstructure On The Temperature mentioning
confidence: 99%
“…Important to understand the measured behavior of the resistance of graphite samples is the existence of well defined interfaces between the single crystalline regions. As we mentioned in the introduction, interfaces between crystalline regions in semiconductors with different orientations for example [20,21,22,23], lead to confined quasi-two dimensional carrier systems with much larger carrier density than the bulk matrix. We assume therefore that these interfaces running parallel to the graphene layers of the graphite structure are the origin of the metallic like resistivity as well as for the apparent large carrier density measured in bulk samples, i.e.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…As the results from various semiconductors show (e.g. n-Ge bicrystals [20,21], p-InSb [22] as well as in Hg 1−x Cd x Te grain boundaries [23]) internal interfaces lead to the formation of confined quasi-two dimensional carrier systems with n 0 ∼ 10 12 . .…”
Section: Introductionmentioning
confidence: 99%